Does Importing Intermediates Increase the Demand for Skilled Workers? Plant-level Evidence from Indonesia - Hiroyuki Kasahara; Yawen Liang; Joel Rodrigue (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper examines whether importing has contributed to skill upgrading among Indonesian plants. Our data records the distribution of years of employee schooling in each plant. We examine how importing affects the demand for highly educated workers within both production and non-production occupation categories at the plant level. We estimate a model of importing and skill-biased technological change in which selection into importing arises due to unobservable heterogenous returns from importing. We find that importing has substantially increased the relative demand for educated production workers, but has had little impact on the demand for educated non-production workers.
Keywords: F16; J23; 330